Hegemony and Legitimacy: US-China Competition in a Contested Indo-Pacific - Cho, Il Hyun (Pacific Affairs, 2025)
Will the escalating competition between the United States and China reshape the evolving regional order in the Indo-Pacific? Existing international relations accounts of regional order in the Indo-Pacific tend to privilege the concept of hegemony. However, regional order is more than the material power attributes of great powers. The central premise of this article is that whether countries in the Indo-Pacific perceive the current regional order as legitimate is as important as the power preponderance of great powers. To secure its long-term and efficient rule over a region, I contend, the regional hegemon should gain and sustain its legitimacy, rather than resorting to the imposition of its will over other nations. While coercive hegemony focuses on the direct, material power attributes of great powers, legitimate hegemony entails the diffuse, social dimension of power. I argue that effective and enduring hegemony is one that is legitimate and thus accepted, not feared, by other nations. The degrees of acceptance of American or Chinese legitimacy by Asian nations in turn shape their preferences for a particular regional order, be it the Indo-Pacific, Asia-Pacific, or Asia. By analyzing the regional perceptions of the types and degrees of legitimacy on the part of the United States and China, this article seeks to explore the connection between legitimacy and regional order and discuss its manifestations in terms of the nature and boundaries of specific regional orders in the contested Indo-Pacific. A systematic account of the regional perceptions of US-China competition is critical to grasping the nature of the evolving and contested regional order in the Indo-Pacific.
Keywords: Coercion; Indo-Pacific; Legitimacy; Middle Powers; Hegemony